A Theoretical Basis for Investigating the Impact of Knowledge Management on Organizational Performance Mediated by Business Intelligence - Rifat O. SHANNAK; Rand K. ABDELHAMID (Communications of International Proceedings, 2022)
Knowledge may be considered a valuable asset that can help businesses attain or sustain a competitive advantage. To achieve actual value from knowledge requires good Knowledge Management (KM). KM refers to the organizational activities and procedures for maximizing its intellectual capabilities by improving the efficacy and efficiency of its knowledge resources. KM comprises a number of processes which can be categorized and simplified into Knowledge creation, Knowledge sharing, and Knowledge utilization. Information systems in turn help organizations survive in the current turbulent business environment. This paper proposes that BI enables and mediates the relationship between KM and organizational performance by influencing and enabling the KM processes. KM processes enabled through BI are expected to have some impact on the organizational performance. This concurs with findings of some previous researches that BI and KM had positive impacts on the organizational performance.
Keywords: Business Intelligence; Knowledge Management; Organizational Performance